Study on Critical Damage Width of Parallel Double-Free Surface Blasting - Shi, Jianjun; Miao, Xiaopeng; Meng, Haili; An, Huaming; Zhang, Wei (Frontiers in Earth Science, 2022)
Reserved rock wall is usually used in blasting operation when one side has an important protection object. Rock wall demolition blasting was essentially a parallel double-free surface blasting; blasting is the ideal effect of casting a side fully broken rock mass, throwing, on the other side (protection) of rock mass at the injury status of “broken and do not come loose”; the minimum thickness of the rock wall last could hole to protect the width of side of the free surface, called the critical damage width. First, based on the theory of multi-boundary blasting, the relationship among the throwing effect, boundary condition, and charge quantity of parallel double-free surface blasting is expounded in this article. The model of equivalent sub-charge package was established to deduce the relationship of bilateral resistance lines, and the theoretical value of critical damage width was 2.05 W (minimum resistance line). Second, according to the rock wall demolition and blasting of the Yangtou station renovation project in the second line of Yuhuai, the critical damage width of 2.5 W was measured through a single row and hole-by-hole detonation field test. The results of study on critical damage width of parallel double-free surface blasting can provide theoretical guidance for similar projects.